ORIGINAL SIN OR ORIGINAL SINFULNESS? A COMMENT - Heans, Simon (Heythrop journal, 2013)
My purpose is to defend Augustine's doctrine of original sin against Joseph Fitzpatrick in his series of articles in New Blackfriars (July 2009–Jan 2010). I begin by arguing that Fitzpatrick's criticisms of it as psychologically inadequate fail because they do not take seriously enough the metaphysical structure of this doctrine, viz, creation from nothing. The second part begins with a critique of Fitzpatrick's interpretation of Genesis 3 and continues with a critical analysis of his proposed alternative to Augustine on original sin (‘original sinfulness’) with reference to the scriptural passages he cites in its support. The conclusion I reach is that ‘original sinfulness’ is not an acceptable biblical hermeneutic. In the third section, I discuss Fitzpatrick's concept of ‘prototypical action’ and, using recent work of Carol Harrison on Augustine's early theological writings, I argue that, far from being incompatible with Augustine's theology of original sin, as Fitzpatrick maintains, this concept enables us to understand Augustine's position in a way that overcomes Fitzpatrick's objections to it.